2015
DOI: 10.15261/serdj.22.169
|View full text |Cite
|
Sign up to set email alerts
|

Reversed Micellar Extraction of Methylene Blue by using Di(2-ethylhexyl) Phosphoric Acid

Abstract: The development of efficient methods for the removal of organic dyes, which are considered to be toxic to the aquatic biota and therefore destroy the ecosystem, is required. In this study, the extraction of methylene blue (MB) from aqueous solution into DEHPA/isooctane solution was investigated. MB was hardly extracted at all from the aqueous to the organic phase at pH values below 5, and the extraction ratio of MB greatly increased with increasing pH in the range of 5-6 by the electrostatic attraction between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Figure 4 shows the effect of AOT and KCl concentration on the K W value of the MB extraction from KCl solution to AOT/EHA solution (C EHA = 100%). It is known that EHA prevents the leakage of DEHPA from an organic phase to an aqueous phase [12]. Although the addition of EHA into an AOT/ isooctane system is not necessary, the effect of the organic solvent was examined in order to compare the AOT and the DEHPA systems.…”
Section: Extraction Kinetics Of Mb By Aotmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 4 shows the effect of AOT and KCl concentration on the K W value of the MB extraction from KCl solution to AOT/EHA solution (C EHA = 100%). It is known that EHA prevents the leakage of DEHPA from an organic phase to an aqueous phase [12]. Although the addition of EHA into an AOT/ isooctane system is not necessary, the effect of the organic solvent was examined in order to compare the AOT and the DEHPA systems.…”
Section: Extraction Kinetics Of Mb By Aotmentioning
confidence: 99%
“…Therefore, it was shown that the extraction rate of MB by AOT or DEHPA is governed by the electrostatic interaction between the MB and extractant, regardless of the size and shape of reverse micelles formed. In the previous paper [12], it was reported that MB was solubilized as a MB-DEHPA complex in the organic solution and/or entrapped in the waterpool of a reverse micelle at pH values above 5.5. From the kinetic study, it was suggested that the positively charged MB was bound to the negatively charged head group of the extractant and solubilized in the organic phase as the MB-extractant complex, rather than MB being taken up by the reverse micelles at the interface.…”
Section: Extraction Kinetics Of Mb By Dehpamentioning
confidence: 99%
See 1 more Smart Citation